Constitutional meaning of Charter of the Country of Kazakhs by Barlybek Syrttanuly (S.B. Alashinsky) - Nurpeyisov Е.К.; Zhussip С.А. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
At the beginning of the twentieth century there were two directions of the national liberation movement in the Kazakh steppe, whose representatives assessed the possible ways of liberation of the Kazakh people from colonial dependence in different ways. The national-religious intelligentsia preferred the Islamization of the population in the family of the Muslim peoples of Russia, which, as a powerful cohesive religious force, would be able to break the chains of colonial dependence and lead the peoples to freedom and independence. Another direction of the national liberation movement is represented by the so-called ‘Westerners’ – the advanced national intelligentsia, which absorbed the ideas and values of the European humanitarian and democratic culture. The ideological foundations and postulates of these movements were fundamentally different, although their ultimate goal – the liberation of the people from colonial dependence, was the same. In strengthening the foundations of the ideology of the "Westerners", the essay on the history of the Kazakhs by A.N. Bukeikhan Kirghiz and the Charter of the Country of the Kazakhs developed by B. Syrttanuly on the initiative of the former played a key role. At the same time, in A. Bukeikhan’s essay, the lands originally inhabited by Kazakhs, and in the Charter of the Country of Kazakhs, the constitutional model of a parliamentary republic is presented, whose jurisdiction should be extended to this territory. Thus, the marginal boundaries of the Kazakhs’ residence were to become the state borders of the Republic of the Country of the Kazakhs.